A radical pluralist philosophy of religion : cross-cultural, multireligious, interdisciplinary - Burley, Mikel, 1972- (London, England : Zed Books, 2020)
"This book is a unique introduction to studying the philosophy of religion, drawing on a wide range of cultures and literary sources in an approach that is both methodologically innovative and expansive in its cross-cultural and multi-religious scope. Employing his expertise in interdisciplinary and Wittgenstein-influenced methods, Mikel Burley draws on works of ethnography and narrative fiction, including Dostoevsky's The Brothers Karamazov and Soyinka's Death and the King's Horseman, to critically engage with existing approaches to the philosophy of religion and advocate a radical, pluralist approach. Breaking away from the standard fixation on a narrow construal of theism, topics discussed include conceptions of compassion in Buddhist ethics, cannibalism in mortuary rituals, divine possession and animal sacrifice in Hindu Goddess worship and animism in indigenous traditions. Original and engaging, Burley's synthesis of philosophical, anthropological and literary elements expands and diversifies the philosophy of religion, providing an essential introduction for anyone interested in studying the radical plurality of forms that religion takes in human life."--
Introduction -- Religious Pluralisms -- Radical Plurality and Critical Description -- Narrative Fiction and Philosophical Inquiry -- 'Compassion beyond Our Imagination': Radical Plurality in Buddhist Ethics -- 'Ways of Being Human': Cannibalism and Respecting the Dead -- 'Awe at the Terrible': Divine Possession, Blood Sacrifice and the Grotesque Body -- 'A Language in Which to Think of the World': Animism, Philosophy and Indigenous Traditions -- Conclusions: Loosening Up Our Lives.
Includes bibliographical references (pages [201]-232) and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Religion -- Philosophy; Philosophy of religion; Electronic books